Modulation of colonic function in irritable bowel syndrome rats by electroacupuncture at ST25 and the neurobiological links between ST25 and the colon - Zhang, Lili; Yu, Cheng; Chen, Biwei; Chao, Yuqiao; Zhang, Haiyan; Zhao, Qinyu; Yang, Kaiwei; Zhang, Yujiao; Chen, Shaozong (Frontiers in Neuroscience, 2022)
Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disease characterized by abdominal pain and defecation disorders. Acupuncture therapy positively affects IBS, with ST25 being the main point. However, ST25 has mostly been used in conjunction with other acupoints. This study aimed to observe the therapeutic effect of electroacupuncture at ST25 alone in IBS and the neurobiological mechanism of ST25 associated with the colon. First, we observed the effect of electroacupuncture at ST25 on the visceral pain threshold and slow-wave discharge of the colon in IBS model rats. Second, we explored the neurobiological mechanism of ST25 associated with the colon using a neural tracer technique. The results showed that (1) electroacupuncture at ST25 alone can alleviate visceral hypersensitivity and restore normal slow-wave frequency and rhythm of the colon in IBS rats; (2) there is a close neuroanatomical connection between ST25 and the colon, i.e., in the dorsal root ganglion (DRG), ST25 is similar in innervation to the colon, mainly in the T8–L1 segment, while the presence of double-labeled positive neurons is present in a part of the DRG; retrogradely labeled motor neurons associated with ST25 were observed in the anterior horn of the spinal cord, and retrogradely labeled sympathetic postganglionic neurons associated with ST25 were observed in the sympathetic nerve chain. These findings suggested that the DRGs and the dorsal horn of the spinal cord are important targets for electroacupuncture at ST25 to reduce visceral hypersensitivity in IBS rats. The sympathetic ganglia may be an important site for ST25 to regulate intestinal motility. The neurobiological mechanism of ST25 action in IBS rats should be further investigated in the future by combining related techniques, such as pseudorabies virus, optogenetics, calcium imaging, and electrophysiology.